Induction and maintenance of healing in erosive esophagitis in the United States. (3rd October 2022) - Yadlapati, Rena; Hubscher, Elizabeth; Pelletier, Corey; Jacob, Rinu; Brackley, Allison; Shah, Shailja
ABSTRACT: Introduction: Erosive esophagitis (EE) occurs when refluxate from the stomach causes T-lymphocyte infiltration of the esophageal mucosa, resulting in mucosal breaks. Currently, therapy with proton-pump inhibitors (PPIs) is the standard treatment for EE in the United States, but few comprehensive reviews exist on the efficacy of PPIs in US populations. Here, we present the most contemporary, thorough analysis of PPI efficacy rates, and identify and characterize patient subgroups at risk for poor healing outcomes. Areas covered: We searched the literature to identify studies reporting rates of endoscopic healing and maintained healing of EE with PPI therapies in the US and found a paucity of recent evidence and real-world evidence. Twenty-two studies from 2009 and earlier were included in the final dataset. Expert opinion: Rates of EE healing with PPIs were highest after 8 weeks of treatment, with over 80% of patients in most treatment arms demonstrating endoscopic healing, compared to lower efficacy (<80%) at 4 weeks. Rates of maintained healing with PPIs at 6 and 12 months were mostly lower than 80%, although the data were limited. Symptomatic patients and those with severe EE were less likely to achieve healing. Obese patients experienced similar healing rates as non-obese patients.